Design and Analyse of a Parallel Connection Model for Hybrid Energy Systems - Guler, Naki; Demirbas, Sevki; Irmak, Erdal (Elektronika ir Elektrotechnika, 2015)
This study proposes a parallel connection method for hybrid renewable energy sources connected on the same bus to obtain an optimum load sharing system among them. Although output voltage of the energy sources connected on the bus changes abruptly, the system continuously adjust the output voltage to a pre-defined constant reference value. Power sharing and voltage fixing operations have been achieved by using PI controllers. The system developed has been simulated for several operating conditions. Simulation results show that the bus voltage are kept constant for all conditions performed and the system reaches steady-state in a very short transient time. DOI: http://dx.doi.org/10.5755/j01.eee.21.2.115012